Impact of COVID-19 Pandemic on Mechanical Reperfusion for Patients With STEMI - De Luca, Giuseppe; Verdoia, Monica; Cercek, Miha; Jensen, Lisette Okkels; Vavlukis, Marija; Calmac, Lucian; Johnson, Tom; Ferrer, Gerard Rourai; Ganyukov, Vladimir; Wojakowski, Wojtek; Kinnaird, Tim; van Birgelen, Clemens; et al. (Elsevier, 2020)
The fear of contagion during the coronavirus disease-2019 (COVID-19) pandemic may have potentially refrained patients with ST-segment elevation myocardial infarction (STEMI) from accessing the emergency system, with subsequent impact on mortality.
Keywords: COVID-19; STEMI; primary angioplasty